Implementasi Internet of Things (IOT) pada Kumbung Jamur Merah Untuk Pemantauan Suhu dan Kelembaban Menggunakan Web Server - Ardiantoro, Nur Faqih; Dalimunthe, Ernando Rizki; Putri, Novia Utami (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2025)
The process of cultivating straw mushrooms in mushroom houses requires strict monitoring of environmental temperature and humidity. In order to make it easier for farmers to monitor temperature and humidity conditions in mushroom barns, the use of Internet of Things (IoT) technology has been proposed as a potential solution. In this research, IoT was implemented on edible mushroom mushrooms to monitor temperature and humidity using a web server as an interface for farmers. The system developed consists of a DHT22 type temperature and humidity sensor connected to an ESP32 microcontroller, which then sends data to a web server via the internet network. The DH22 sensor can display accurate measurement data both on the LCD and on the web server. Therefore, the system developed is able to monitor the environmental conditions of mushroom mushrooms and provide useful information for farmers in the process of cultivating mushrooms more efficiently.